2005
DOI: 10.1016/j.cardiores.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The NR4A subfamily of nuclear receptors: new early genes regulated by growth factors in vascular cells

Abstract: The molecular mechanisms regulating endothelial cell activation and vascular smooth muscle cell proliferation are critical in the pathological processes underlying atherosclerosis. Numerous growth factors and cytokines trigger the complex and redundant signaling pathways that regulate cell cycle entry; however, the genes controlling these processes are not fully known. Applying techniques for differential gene expression analysis, new transcription factors have been identified in these mechanisms, among them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 93 publications
1
133
0
Order By: Relevance
“…Binding of LTD 4 to cysLT 2 -R activates genes that have not previously been associated with the action of cysLTs. These include transcription factors that participate in ischemic stress and reperfusion injury in mice (24)(25)(26)(27) (EGR1 and NR4A); chemokines and cell-adhesion molecules involved in blood leukocyte recruitment to inflamed tissues (28)(29)(30)43) (CXCL2, IL-8, and SELE); an extracellular matrix-degrading metalloprotease implicated in carotid artery remodeling (44) and degradation of the collagen-binding proteoglycans versican and aggrecan (32) (ADAMTS1), a potent endogenous inhibitor of calcineurin signaling (31) (DSCR1), the key regulator of the extrinsic blood coagulation cascade (42) (TF), and a key prostaglandin synthesis-regulating enzyme (33) (COX-2). These data show that cysLTs initiate activities through robust induction of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of LTD 4 to cysLT 2 -R activates genes that have not previously been associated with the action of cysLTs. These include transcription factors that participate in ischemic stress and reperfusion injury in mice (24)(25)(26)(27) (EGR1 and NR4A); chemokines and cell-adhesion molecules involved in blood leukocyte recruitment to inflamed tissues (28)(29)(30)43) (CXCL2, IL-8, and SELE); an extracellular matrix-degrading metalloprotease implicated in carotid artery remodeling (44) and degradation of the collagen-binding proteoglycans versican and aggrecan (32) (ADAMTS1), a potent endogenous inhibitor of calcineurin signaling (31) (DSCR1), the key regulator of the extrinsic blood coagulation cascade (42) (TF), and a key prostaglandin synthesis-regulating enzyme (33) (COX-2). These data show that cysLTs initiate activities through robust induction of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). The EGR and NR4A families were chosen for detailed analyses because they may contribute to inflammation, EGR1 can induce TF by transactivating the TF promoter, and EGR1 has been shown to mediate oxidative stress-induced vascular reperfusion injury (24)(25)(26)(27). Members of the EGR and NR4A families were among the most strongly up-regulated genes, as judged by the fold change of signal intensities of the corresponding probe sets (Table 1).…”
Section: Ltd4 Stimulates Early Growth Response (Egr) and Nuclear Recementioning
confidence: 99%
“…Among the growth factor-responsive transcription factors that translate mitogenic cues to VSMC proliferation, members of the NR4A subfamily of orphan nuclear receptors have emerged as key regulators of vascular gene expression (15)(16)(17). This subfamily functions as immediate early response genes, which are rapidly induced by a pleiotropy of stimuli to modulate important cellular functions, including proliferation and apoptosis (15)(16)(17). NR4A receptors transactivate target promoters by binding to different variations of the canonical NGFI-B response element (NBRE) (15)(16)(17).…”
Section: Vascular Smooth Muscle Cells (Vsmc)mentioning
confidence: 99%
“…The NR4A subfamily has subsequently been implicated in biological and pathophysiological contexts such as immune development, immunological disorders, neuroendocrine regulation, liver regeneration and cancer (Scearce et al, 1993;Zhou et al, 1996;Zetterstrom et al, 1997;Li et al, 1998;Murphy et al, 2001). Recently, NR4A subfamily members have emerged as potentially important factors in the complex network of proteins that regulate endothelial cell activation and vascular smooth muscle cell (VSMC) proliferation, their role has been implicated in vascular diseases such as atherosclerosis (Arkenbout et al, 2002;Gruber et al, 2003;Martinez-Gonzalez et al, 2003;Martinez-Gonzalez and Badimon, 2005;Rius et al, 2006). In the previous study, we reported that Nur77 has a novel function that enhances the transcriptional activity of HIF-1a by stabilizing the protein (Yoo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%